High-conductivity lithium iron phosphate material and preparation method thereof

By introducing conductive network components and optimizing the preparation process into lithium iron phosphate materials, the insufficient performance of lithium iron phosphate materials under high-rate charging and discharge conditions is solved, and the high conductivity and excellent cycling stability and rate performance of the material are achieved.

CN119581532AActive Publication Date: 2025-03-07SHANDONG GOLDENCELL ELECTRONICS TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411779100.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The low electronic conductivity and ion diffusion coefficient of lithium iron phosphate materials limit their performance under high-rate charging and discharging conditions, especially in cases of rapid start-up and acceleration.

Method used

By introducing graphene, gas-phase-grown carbon fibers, carbon nanotubes and precious metal precursors into lithium iron phosphate materials, an effective conductive network is formed, and the optimized preparation process includes spray drying and high-temperature sintering.

Benefits of technology

It significantly improves the conductivity and lithium ion diffusion rate of lithium iron phosphate materials, improves the performance of the material under high-rate charging and discharging conditions, and meets the instantaneous high current demand for rapid start-up and acceleration of electric vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581532A_ABST
    Figure CN119581532A_ABST
Patent Text Reader

Abstract

The invention discloses a high-conductivity lithium iron phosphate material and a preparation method thereof, and belongs to the technical field of lithium iron phosphate, and the high-conductivity lithium iron phosphate material comprises the following components in percentage by mass: 88%-92% of lithium iron phosphate, 2%-4% of graphene, 0.5%-1.5% of vapor-phase growth carbon fiber, 0.5%-1% of a noble metal precursor, 2%-5% of a carbon nanotube and 0.1%-0.5% of a dopant. By introducing the graphene, the vapor-grown carbon fibers, the carbon nanotubes and the noble metal precursor, an effective conductive network can be formed, and the network not only enhances the electronic conductivity of the material, but also promotes the diffusion rate of lithium ions in the material; specifically, the graphene and the carbon nanotubes provide a continuous electron conduction path and reduce charge transfer resistance, and the vapor-grown carbon fibers construct a stable conductive skeleton on a microscopic level to ensure that the material can maintain good electron conductivity even under high compaction density; the performance of the material under high-rate charge and discharge conditions is directly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium iron phosphate, and in particular relates to a high-conductivity lithium iron phosphate material and a preparation method thereof. Background Art

[0002] Lithium iron phosphate (LiFePO4), as a positive electrode material for lithium-ion batteries, has a stable crystal structure and can maintain structural integrity during the charge and discharge process, thus ensuring a long cycle life of the battery. At the same time, lithium iron phosphate has high thermal stability and is not prone to thermal runaway, so it has high safety. In addition, due to its rich and non-toxic composition, lithium iron phosphate is also environmentally friendly. These characteristics make lithium iron phosphate an ideal choice for applications such as electric vehicles and large-scale energy storage systems.

[0003] However, the electronic conductivity and ion diffusion coefficient of lithium iron phosphate materials are low, which limits its performance under high-rate charge and discharge conditions; under high-rate discharge conditions, the battery needs to quickly transmit electrons and lithium ions to meet the needs of large currents; however, these properties of lithium iron phosphate limit its performance in fast charge and discharge applications, especially in situations where a large amount of energy needs to be provided in a short period of time, such as the rapid start and acceleration of electric vehicles. Therefore, we propose a high-conductivity lithium iron phosphate material and a preparation method. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the deficiencies in the prior art, the present invention provides a high-conductivity lithium iron phosphate material and a preparation method. By optimizing the material formula and preparation process, the conductivity of lithium iron phosphate is significantly improved, and the problem that the existing lithium iron phosphate materials often involve complex process steps and require precise control of the type and concentration of doping elements, as well as the thickness and uniformity of the carbon coating; these requirements not only increase the difficulty of the production process, but also increase the manufacturing cost.

[0006] (II) Technical solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] A high-conductivity lithium iron phosphate material comprises the following components, measured by mass percentage: 88% to 92% lithium iron phosphate, 2% to 4% graphene, 0.5% to 1.5% vapor-grown carbon fiber, 0.5% to 1% noble metal precursor, 2% to 5% carbon nanotubes and 0.1% to 0.5% dopant, with the balance being deionized water.

[0009] Furthermore, the noble metal precursor is palladium chloride.

[0010] Furthermore, the dopant is one of boron, nitrogen and fluorine, or a mixture of more than one of them.

[0011] A method for preparing a high-conductivity lithium iron phosphate material comprises the following steps:

[0012] S1: fully mixing lithium iron phosphate, graphene, vapor-grown carbon fiber, noble metal precursor, carbon nanotube and dopant in deionized water for 2 to 3 hours to obtain a mixed slurry;

[0013] S2: drying the mixed slurry obtained in step S1 by spray drying to obtain a dry precursor material, wherein the air inlet temperature during the spray drying process is 150-250° C. and the atomization pressure is 2-5 bar;

[0014] S3: sintering the dried precursor material at high temperature in a nitrogen or argon atmosphere to obtain a high-conductivity lithium iron phosphate material, wherein the purity of the nitrogen or argon is not less than 99.99%;

[0015] Furthermore, the high conductivity lithium iron phosphate material prepared by S3 was subjected to the first discharge capacity test: at a current density of 0.1C, the first discharge capacity was ≥160mAh / g.

[0016] Furthermore, the high conductivity lithium iron phosphate material prepared by S3 was subjected to a cycle stability test: at a current density of 1C, the discharge capacity retention rate after 100 cycles was ≥95%.

[0017] Furthermore, the rate performance test of the high conductivity lithium iron phosphate material prepared by S3 was carried out:

[0018] At 0.1C current density, the first discharge capacity is ≥160mAh / g;

[0019] At a current density of 0.5C, the discharge capacity is not less than 90% of the initial discharge capacity;

[0020] At 1C current density, the discharge capacity is not less than 85% of the initial discharge capacity;

[0021] At 2C current density, the discharge capacity is not less than 80% of the initial discharge capacity;

[0022] At a current density of 5C, the discharge capacity is not less than 60% of the initial discharge capacity.

[0023] Furthermore, in the step S3, the high temperature sintering temperature is 700-800° C., and the sintering time is 10-12 hours.

[0024] Furthermore, the D50 particle size of the high-conductivity lithium iron phosphate material prepared in step S3 is 10 to 30 μm.

[0025] Furthermore, in S1, the solid content of the mixed slurry is 30% to 50%.

[0026] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:

[0027] 1. The present invention can form an effective conductive network by introducing graphene, vapor-grown carbon fiber, carbon nanotubes and precious metal precursors into lithium iron phosphate materials. This conductive network not only enhances the electronic conductivity of the material itself, but also promotes the diffusion rate of lithium ions in the material. Specifically, graphene and carbon nanotubes provide a continuous electron conduction path, reducing the charge transfer resistance, while the vapor-grown carbon fiber constructs a stable conductive skeleton at the microscopic level, ensuring that the material can maintain good electronic conductivity even at a high compaction density. This directly improves the performance of the material under high-rate charge and discharge conditions, and meets the instantaneous large current requirements required for rapid start-up and acceleration of electric vehicles.

[0028] 2. The present invention adopts a specific high-temperature sintering step in the preparation process and performs sintering at 700-800°C in a nitrogen or argon atmosphere. This not only ensures the purity of the material, but also optimizes the size and morphology of the lithium iron phosphate particles by controlling the sintering conditions, so that the particle size distribution of the final product is concentrated in the range of D50=10-30μm. This particle size range is beneficial to improving the electrochemical properties of the material, especially improving the first discharge capacity and the discharge capacity retention rate at different current densities, thereby improving the cycle stability and rate performance of the material under high-rate charge and discharge conditions.

[0029] 3. The present invention significantly improves the conductivity of lithium iron phosphate materials by optimizing material formula and preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the preparation step of the high conductivity lithium iron phosphate material of the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] A high-conductivity lithium iron phosphate material comprises the following components, measured by mass percentage: 90% lithium iron phosphate, 3% graphene, 1% vapor-grown carbon fiber, 0.8% noble metal precursor, 4% carbon nanotubes and 0.3% dopant, with the balance being deionized water.

[0034] The noble metal precursor is palladium chloride.

[0035] The dopant is boron.

[0036] A method for preparing a high-conductivity lithium iron phosphate material comprises the following steps:

[0037] S1: lithium iron phosphate, graphene, vapor-grown carbon fiber, noble metal precursor, carbon nanotubes and dopant were fully mixed in deionized water, and stirred for 3 h using a high-speed stirrer to obtain a mixed slurry, and the solid content was recorded as 45%;

[0038] S2: drying the mixed slurry obtained in step S1 by spray drying, with an air inlet temperature of 180°C and an atomization pressure of 3 bar to obtain a dry precursor material, and the spray drying time is 45 minutes;

[0039] The spray drying method in S2 comprises the following steps:

[0040] Q1: Preheat the dryer: Preheat the spray dryer to the set air inlet temperature;

[0041] Q2: Slurry preparation: prepare the mixed slurry;

[0042] Q3: Slurry delivery: Use a pump to deliver the mixed slurry from the storage tank to the spray head of the spray dryer;

[0043] Q4: Spray drying: In the preheated dryer, the mixed slurry is atomized through a spray head to form fine droplets;

[0044] Q5: Hot air circulation: The hot air is circulated through the spray tower by the fan, so that the droplets are fully in contact with the hot air, accelerating the evaporation of water to obtain dry precursor materials;

[0045] Q6: Powder collection: The dried precursor material is collected through a bag filter;

[0046] Q7: Product cooling: Cool the collected precursor material to room temperature.

[0047] S3: The precursor material obtained in step Q7 is subjected to high-temperature sintering in a nitrogen or argon atmosphere to obtain a high-conductivity lithium iron phosphate material, the high-temperature sintering temperature is 750°C, the sintering time is 12 hours, wherein the content of nitrogen or argon is 99.99% of the total gas volume in the container, and the D50 particle size of the prepared high-conductivity lithium iron phosphate material is 20 μm;

[0048] S4: Use an electrochemical analysis station and a lithium battery test system to test the electrical properties of the high-conductivity lithium iron phosphate material prepared in S3. The test items include the first discharge capacity, cycle stability, and rate performance.

[0049] The electrical performance test in S4 includes the following steps:

[0050] First discharge capacity: At a current density of 0.1C, the first discharge capacity of the high conductivity lithium iron phosphate material prepared by S3 was tested;

[0051] Cycle stability: 100 cycles were performed at a current density of 1C to test the capacity retention rate of the high-conductivity lithium iron phosphate material prepared by S3;

[0052] Rate performance: The discharge capacity of the high conductivity lithium iron phosphate material product prepared by S3 was tested at current densities of 0.1C, 0.5C, 1C, 2C and 5C.

[0053] The results of the electrical performance test are shown in Table 1.

[0054] Table 1

[0055]

[0056]

[0057] S5: The high conductivity lithium iron phosphate material prepared in S3 was tested for its specific surface area using a surface area analyzer, and then its pore volume and average pore size were tested using a porosity analyzer. The test results are shown in Table 2.

[0058] Experimental steps:

[0059] Step 1: Specific surface area analysis: Use a specific surface area analyzer to measure the specific surface area of ​​the sample in this embodiment;

[0060] Step 2: Pore structure analysis: Use a porosity analyzer to measure the pore volume and average pore size of the sample.

[0061] Table 2

[0062]

[0063] Embodiment 2:

[0064] A high-conductivity lithium iron phosphate material comprises the following components, measured by mass percentage: 92% lithium iron phosphate, 2% graphene, 1.5% vapor-grown carbon fiber, 0.5% noble metal precursor, 2% nanotubes and 0.1% dopant, with the balance being deionized water.

[0065] The noble metal precursor is palladium chloride.

[0066] The dopant is fluorine.

[0067] A method for preparing a high-conductivity lithium iron phosphate material comprises the following steps:

[0068] S1: lithium iron phosphate, graphene, vapor-grown carbon fiber, noble metal precursor, carbon nanotubes and dopant are fully mixed in deionized water, and stirred for 2 h using a high-speed stirrer to obtain a mixed slurry, and the solid content is recorded as 30%;

[0069] S2: Dry the mixed slurry obtained in step S1 by spray drying (same as in Example 1), with an air inlet temperature of 150° C. and an atomization pressure of 2 bar to obtain a dry precursor material, and the spray drying time is min;

[0070] S3: The precursor material obtained in step Q7 is subjected to high-temperature sintering in a nitrogen or argon atmosphere to obtain a high-conductivity lithium iron phosphate material, the high-temperature sintering temperature is 700°C, the sintering time is 10 hours, wherein the content of nitrogen or argon is 99.99% of the total gas volume in the container, and the D50 particle size of the prepared high-conductivity lithium iron phosphate material is 15 μm;

[0071] S4: Using an electrochemical analysis station and a lithium battery testing system to test the electrical properties of the high conductivity lithium iron phosphate material prepared in S3, the test items include the first discharge capacity, cycle stability and rate performance, the test method is the same as in Example 1, and the results are shown in Table 3;

[0072] Table 3

[0073]

[0074]

[0075] S5: The high conductivity lithium iron phosphate material prepared in S3 was tested for its specific surface area using a surface area analyzer, and then its pore volume and average pore diameter were tested using a porosity analyzer. The testing method was the same as in Example 1, and the test results are shown in Table 4.

[0076] Table 4

[0077]

[0078] Embodiment 3:

[0079] A high-conductivity lithium iron phosphate material comprises the following components, measured by mass percentage: 88% lithium iron phosphate, 4% graphene, 0.5% vapor-grown carbon fiber, 1% noble metal precursor, 5% carbon nanotubes and 0.5% dopant, with the balance being deionized water.

[0080] The noble metal precursor is palladium chloride.

[0081] The dopant is nitrogen.

[0082] A method for preparing a high-conductivity lithium iron phosphate material comprises the following steps:

[0083] S1: lithium iron phosphate, graphene, vapor-grown carbon fiber, noble metal precursor, carbon nanotube and dopant are fully mixed in deionized water, and stirred for 3 h using a high-speed stirrer to obtain a mixed slurry, and the solid content is recorded as 50%;

[0084] S2: Dry the mixed slurry obtained in step S1 by spray drying (same as in Example 1), with an air inlet temperature of 250° C. and an atomization pressure of 5 bar to obtain a dry precursor material, and the spray drying time is min;

[0085] S3: The precursor material obtained in step Q7 is subjected to high-temperature sintering in a nitrogen or argon atmosphere to obtain a high-conductivity lithium iron phosphate material, the high-temperature sintering temperature is 800° C., the sintering time is 12 hours, wherein the content of nitrogen or argon is 99.99% of the total gas volume in the container, and the D50 particle size of the prepared high-conductivity lithium iron phosphate material is 25 μm;

[0086] S4: Using an electrochemical analysis station and a lithium battery testing system, the electrical performance of the high conductivity lithium iron phosphate material prepared in S3 was tested, including the first discharge capacity, cycle stability and rate performance. The testing method was the same as in Example 1. The results are shown in Table 7.

[0087] Table 5

[0088]

[0089] S5: The high conductivity lithium iron phosphate material prepared in S3 was tested for its specific surface area using a surface area analyzer, and then its pore volume and average pore diameter were tested using a porosity analyzer. The testing method was the same as in Example 1, and the test results are shown in Table 8.

[0090] Table 6

[0091]

[0092]

[0093] Comparative Example 1

[0094] Different from Example 1, the calcination temperature in step S3 is 600°C.

[0095] A high-conductivity lithium iron phosphate material comprises the following components, measured by mass percentage: 90% lithium iron phosphate, 3% graphene, 1% vapor-grown carbon fiber, 0.8% noble metal precursor, 4% carbon nanotubes and 0.3% dopant, with the balance being deionized water.

[0096] The noble metal precursor is palladium chloride.

[0097] The dopant is boron.

[0098] A method for preparing a high-conductivity lithium iron phosphate material comprises the following steps:

[0099] S1: lithium iron phosphate, graphene, vapor-grown carbon fiber, noble metal precursor, carbon nanotubes and dopant were fully mixed in deionized water, and stirred for 3 h using a high-speed stirrer to obtain a mixed slurry, and the solid content was recorded as 45%;

[0100] S2: drying the mixed slurry obtained in step S1 by spray drying, with an air inlet temperature of 180°C and an atomization pressure of 3 bar to obtain a dry precursor material, and the spray drying time is 45 minutes;

[0101] The spray drying method in S2 comprises the following steps:

[0102] Q1: Preheat the dryer: Preheat the spray dryer to the set air inlet temperature;

[0103] Q2: Slurry preparation: prepare the mixed slurry;

[0104] Q3: Slurry delivery: Use a pump to deliver the mixed slurry from the storage tank to the spray head of the spray dryer;

[0105] Q4: Spray drying: In the preheated dryer, the mixed slurry is atomized through a spray head to form fine droplets;

[0106] Q5: Hot air circulation: The hot air is circulated through the spray tower by the fan, so that the droplets are fully in contact with the hot air, accelerating the evaporation of water to obtain dry precursor materials;

[0107] Q6: Powder collection: The dried precursor material is collected through a bag filter;

[0108] Q7: Product cooling: Cool the collected precursor material to room temperature.

[0109] S3: The precursor material obtained in step Q7 is subjected to high-temperature sintering in a nitrogen or argon atmosphere to obtain a high-conductivity lithium iron phosphate material, the high-temperature sintering temperature is 600° C., the sintering time is 12 h, wherein the content of nitrogen or argon is 99.99% of the total gas volume in the container, and the D50 particle size of the prepared high-conductivity lithium iron phosphate material is 12 μm;

[0110] S4: The electrical performance of the high conductivity lithium iron phosphate material prepared in S3 was tested using an electrochemical analysis station and a lithium battery testing system. The test items included the first discharge capacity, cycle stability and rate performance. The results of the electrical performance test are shown in Table 7.

[0111] Table 7

[0112]

[0113]

[0114] S5: The high conductivity lithium iron phosphate material prepared in S3 was tested for its specific surface area using a surface area analyzer, and then its pore volume and average pore diameter were tested using a porosity analyzer. The test results are shown in Table 8.

[0115] Table 8

[0116]

[0117] Comparative Example 2

[0118] Different from Example 1, the calcination temperature in step S3 is 900°C.

[0119] A high-conductivity lithium iron phosphate material comprises the following components, measured by mass percentage: 90% lithium iron phosphate, 3% graphene, 1% vapor-grown carbon fiber, 0.8% noble metal precursor, 4% carbon nanotubes and 0.3% dopant, with the balance being deionized water.

[0120] The noble metal precursor is palladium chloride.

[0121] The dopant is boron.

[0122] A method for preparing a high-conductivity lithium iron phosphate material comprises the following steps:

[0123] S1: lithium iron phosphate, graphene, vapor-grown carbon fiber, noble metal precursor, carbon nanotubes and dopant were fully mixed in deionized water, and stirred for 3 h using a high-speed stirrer to obtain a mixed slurry, and the solid content was recorded as 45%;

[0124] S2: drying the mixed slurry obtained in step S1 by spray drying, with an air inlet temperature of 180°C and an atomization pressure of 3 bar to obtain a dry precursor material, and the spray drying time is 45 minutes;

[0125] The spray drying method in S2 comprises the following steps:

[0126] Q1: Preheat the dryer: Preheat the spray dryer to the set air inlet temperature;

[0127] Q2: Slurry preparation: prepare the mixed slurry;

[0128] Q3: Slurry delivery: Use a pump to deliver the mixed slurry from the storage tank to the spray head of the spray dryer;

[0129] Q4: Spray drying: In the preheated dryer, the mixed slurry is atomized through a spray head to form fine droplets;

[0130] Q5: Hot air circulation: The hot air is circulated through the spray tower by the fan, so that the droplets are fully in contact with the hot air, accelerating the evaporation of water to obtain dry precursor materials;

[0131] Q6: Powder collection: The dried precursor material is collected through a bag filter;

[0132] Q7: Product cooling: Cool the collected precursor material to room temperature.

[0133] S3: The precursor material obtained in step Q7 is subjected to high-temperature sintering in a nitrogen or argon atmosphere to obtain a high-conductivity lithium iron phosphate material, the high-temperature sintering temperature is 900° C., the sintering time is 12 h, wherein the content of nitrogen or argon is 99.99% of the total gas volume in the container, and the D50 particle size of the prepared high-conductivity lithium iron phosphate material is 18 μm;

[0134] S4: Use an electrochemical analysis station and a lithium battery test system to test the electrical properties of the high conductivity lithium iron phosphate material prepared in S3. The test items include the first discharge capacity, cycle stability and rate performance. The results of the electrical properties test are shown in Table 9.

[0135] Table 9

[0136]

[0137]

[0138] S5: The high conductivity lithium iron phosphate material prepared in S3 was tested for its specific surface area using a surface area analyzer, and then its pore volume and average pore diameter were tested using a porosity analyzer. The test results are shown in Table 10.

[0139] Table 10

[0140]

[0141] Comparative Example 3

[0142] Different from Example 1, Comparative Example 3 does not contain a dopant.

[0143] A high-conductivity lithium iron phosphate material comprises the following components, measured by mass percentage: 90% lithium iron phosphate, 3% graphene, 1% vapor-grown carbon fiber, 0.8% noble metal precursor and 4% carbon nanotube, with the balance being deionized water.

[0144] The noble metal precursor is palladium chloride.

[0145] A method for preparing a high-conductivity lithium iron phosphate material comprises the following steps:

[0146] S1: lithium iron phosphate, graphene, vapor-grown carbon fiber, noble metal precursor and carbon nanotubes were fully mixed in deionized water and stirred for 3 h using a high-speed stirrer to obtain a mixed slurry with a solid content of 45%;

[0147] S2: drying the mixed slurry obtained in step S1 by spray drying, with an air inlet temperature of 180°C and an atomization pressure of 3 bar to obtain a dry precursor material, and the spray drying time is 45 minutes;

[0148] The spray drying method in S2 comprises the following steps:

[0149] Q1: Preheat the dryer: Preheat the spray dryer to the set air inlet temperature;

[0150] Q2: Slurry preparation: prepare the mixed slurry;

[0151] Q3: Slurry delivery: Use a pump to deliver the mixed slurry from the storage tank to the spray head of the spray dryer;

[0152] Q4: Spray drying: In the preheated dryer, the mixed slurry is atomized through a spray head to form fine droplets;

[0153] Q5: Hot air circulation: The hot air is circulated through the spray tower by the fan, so that the droplets are fully in contact with the hot air, accelerating the evaporation of water to obtain dry precursor materials;

[0154] Q6: Powder collection: The dried precursor material is collected through a bag filter;

[0155] Q7: Product cooling: Cool the collected precursor material to room temperature.

[0156] S3: The precursor material obtained in step Q7 is subjected to high-temperature sintering in a nitrogen or argon atmosphere to obtain a high-conductivity lithium iron phosphate material, the high-temperature sintering temperature is 750°C, the sintering time is 12 hours, wherein the content of nitrogen or argon is 99.99% of the total gas volume in the container, and the D50 particle size of the prepared high-conductivity lithium iron phosphate material is 13 μm;

[0157] S4: Use an electrochemical analysis station and a lithium battery test system to test the electrical properties of the high-conductivity lithium iron phosphate material prepared in S3. The test items include the first discharge capacity, cycle stability, and rate performance.

[0158] The electrical performance test in S4 includes the following steps:

[0159] First discharge capacity: At a current density of 0.1C, the first discharge capacity of the high conductivity lithium iron phosphate material prepared by S3 was tested;

[0160] Cycle stability: 100 cycles were performed at a current density of 1C to test the capacity retention rate of the high-conductivity lithium iron phosphate material prepared by S3;

[0161] Rate performance: The discharge capacity of the high conductivity lithium iron phosphate material product prepared by S3 was tested at current densities of 0.1C, 0.5C, 1C, 2C and 5C.

[0162] The results of the electrical performance test are shown in Table 1.

[0163] Table 11

[0164]

[0165] S5: The high conductivity lithium iron phosphate material prepared in S3 was tested for its specific surface area using a surface area analyzer, and then its pore volume and average pore size were tested using a porosity analyzer. The test results are shown in Table 2.

[0166] Experimental steps:

[0167] Step 1: Specific surface area analysis: Use a specific surface area analyzer to measure the specific surface area of ​​the sample in this embodiment;

[0168] Step 2: Pore structure analysis: Use a porosity analyzer to measure the pore volume and average pore size of the sample.

[0169] Table 12

[0170]

[0171] Comparative Example 4

[0172] Different from Example 1, no dopant is added, and the calcination temperature in step S3 is 600°C.

[0173] A high-conductivity lithium iron phosphate material comprises the following components, measured by mass percentage: 90% lithium iron phosphate, 3% graphene, 1% vapor-grown carbon fiber, 0.8% noble metal precursor and 4% carbon nanotube, with the balance being deionized water.

[0174] The noble metal precursor is palladium chloride.

[0175] A method for preparing a high-conductivity lithium iron phosphate material comprises the following steps:

[0176] S1: lithium iron phosphate, graphene, vapor-grown carbon fiber, noble metal precursor and carbon nanotubes were fully mixed in deionized water and stirred for 3 h using a high-speed stirrer to obtain a mixed slurry with a solid content of 45%;

[0177] S2: drying the mixed slurry obtained in step S1 by spray drying, with an air inlet temperature of 180°C and an atomization pressure of 3 bar to obtain a dry precursor material, and the spray drying time is 45 minutes;

[0178] The spray drying method in S2 comprises the following steps:

[0179] Q1: Preheat the dryer: Preheat the spray dryer to the set air inlet temperature;

[0180] Q2: Slurry preparation: prepare the mixed slurry;

[0181] Q3: Slurry delivery: Use a pump to deliver the mixed slurry from the storage tank to the spray head of the spray dryer;

[0182] Q4: Spray drying: In the preheated dryer, the mixed slurry is atomized through a spray head to form fine droplets;

[0183] Q5: Hot air circulation: The hot air is circulated through the spray tower by the fan, so that the droplets are fully in contact with the hot air, accelerating the evaporation of water to obtain dry precursor materials;

[0184] Q6: Powder collection: The dried precursor material is collected through a bag filter;

[0185] Q7: Product cooling: Cool the collected precursor material to room temperature.

[0186] S3: The precursor material obtained in step Q7 is subjected to high-temperature sintering in a nitrogen or argon atmosphere to obtain a high-conductivity lithium iron phosphate material, the high-temperature sintering temperature is 600°C, the sintering time is 12 hours, wherein the content of nitrogen or argon is 99.99% of the total gas volume in the container, and the D50 particle size of the prepared high-conductivity lithium iron phosphate material is 9 μm;

[0187] S4: Use an electrochemical analysis station and a lithium battery test system to test the electrical properties of the high-conductivity lithium iron phosphate material prepared in S3. The test items include the first discharge capacity, cycle stability, and rate performance.

[0188] The electrical performance test in S4 includes the following steps:

[0189] First discharge capacity: At a current density of 0.1C, the first discharge capacity of the high conductivity lithium iron phosphate material prepared by S3 was tested;

[0190] Cycle stability: 100 cycles were performed at a current density of 1C to test the capacity retention rate of the high-conductivity lithium iron phosphate material prepared by S3;

[0191] Rate performance: The discharge capacity of the high conductivity lithium iron phosphate material product prepared by S3 was tested at current densities of 0.1C, 0.5C, 1C, 2C and 5C.

[0192] The results of the electrical performance tests are shown in Tables 13 and 14.

[0193] Table 13

[0194]

[0195] S5: The high conductivity lithium iron phosphate material prepared in S3 was tested for its specific surface area using a surface area analyzer, and then its pore volume and average pore size were tested using a porosity analyzer. The test results are shown in Table 2.

[0196] Experimental steps:

[0197] Step 1: Specific surface area analysis: Use a specific surface area analyzer to measure the specific surface area of ​​the sample in this embodiment;

[0198] Step 2: Pore structure analysis: Use a porosity analyzer to measure the pore volume and average pore size of the sample.

[0199] Table 14

[0200]

[0201] Result analysis:

[0202] 1. Combining the data in Table 1, Table 3 and Table 5, the electrical property test results of the high conductivity lithium iron phosphate materials prepared by Examples 1 to 3 show that the high conductivity lithium iron phosphate materials prepared by the technical solution have good electrochemical properties, the first discharge capacity is not less than 165 mAh / g, the capacity retention rate after 100 cycles at a current density of 1C is not less than 95%, the discharge capacity at different current densities meets the requirements, and shows excellent cycle stability and rate performance.

[0203] 2. Combining the data in Table 2, Table 4 and Table 6, it can be seen from the physical property test results of the high conductivity lithium iron phosphate materials prepared in Examples 1 to 3 that the high conductivity lithium iron phosphate material has a high specific surface area, pore volume and suitable average pore size, and the high conductivity lithium iron phosphate material prepared by the present invention has excellent physical properties.

[0204] 3. In step S2 of comparative example 1 and comparative example 2, high-temperature calcination is carried out at 600°C and 900°C, respectively. Combined with the data in Tables 7 to 10, the physical property test and the conductive property test of the high conductivity lithium iron phosphate materials prepared in comparative example 1 and comparative example 2 are lower than the test results of the physical property test and the conductive property test of the high conductivity lithium iron phosphate material prepared in Example 1, indicating that the appropriate calcination temperature of the precursor material in step S2 improves the electrochemical properties of the high conductivity lithium iron phosphate material, and the sintering temperature is too high or too low, which will reduce the electrochemical properties of the high conductivity lithium iron phosphate material finally prepared.

[0205] At the same time, no dopant was added in Comparative Example 3, and the calcination temperature of step S3 of Comparative Example 4 was 600°C based on Comparative Example 3. Combining the data in Comparative Example 1 and Tables 7, 8, 11, 12, 13 and 14, it can be seen that the dopant can best improve the conductivity of the prepared lithium iron phosphate when the calcination temperature is greater than 700°C.

[0206] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A high conductivity lithium iron phosphate material, characterized in that: Calculated by mass percentage, the invention comprises the following components: 88% to 92% lithium iron phosphate, 2% to 4% graphene, 0.5% to 1.5% vapor-grown carbon fiber, 0.5% to 1% noble metal precursor, 2% to 5% carbon nanotube and 0.1% to 0.5% dopant, and the balance is deionized water.

2. A high conductivity lithium iron phosphate material according to claim 1, characterized in that: The noble metal precursor is palladium chloride.

3. The high conductivity lithium iron phosphate material according to claim 1, characterized in that: The dopant is one of boron, nitrogen and fluorine or a mixture of more than one of them.

4. A method for preparing a high conductivity lithium iron phosphate material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: fully mixing lithium iron phosphate, graphene, vapor-grown carbon fiber, noble metal precursor, carbon nanotube and dopant in deionized water for 2 to 3 hours to obtain a mixed slurry; S2: drying the mixed slurry obtained in step S1 by spray drying to obtain a dry precursor material, wherein the air inlet temperature during the spray drying process is 150-250° C. and the atomization pressure is 2-5 bar; S3: sintering the dried precursor material at high temperature in a nitrogen or argon atmosphere to obtain a high-conductivity lithium iron phosphate material, wherein the purity of the nitrogen or argon atmosphere is not less than 99.99%.

5. The method for preparing a high conductivity lithium iron phosphate material according to claim 4, characterized in that: The first discharge capacity test was carried out on the high conductivity lithium iron phosphate material prepared by S3: at a current density of 0.1C, the first discharge capacity was ≥160mAh / g.

6. The method for preparing a high conductivity lithium iron phosphate material according to claim 4, characterized in that: The high conductivity lithium iron phosphate material prepared by S3 was subjected to a cycle stability test: at a current density of 1C, the discharge capacity retention rate after 100 cycles was ≥95%.

7. The method for preparing a high conductivity lithium iron phosphate material according to claim 4, characterized in that: The rate performance test of the high conductivity lithium iron phosphate material prepared by S3 was carried out: At 0.1C current density, the first discharge capacity is ≥160mAh / g; At a current density of 0.5C, the discharge capacity is not less than 90% of the initial discharge capacity; At 1C current density, the discharge capacity is not less than 85% of the initial discharge capacity; At 2C current density, the discharge capacity is not less than 80% of the initial discharge capacity; At a current density of 5C, the discharge capacity is not less than 60% of the initial discharge capacity.

8. The method for preparing a high conductivity lithium iron phosphate material according to claim 4, characterized in that: In the step S3, the high temperature sintering temperature is 700-800° C., and the sintering time is 10-12 hours.

9. The method for preparing a high conductivity lithium iron phosphate material according to claim 4, characterized in that: The D50 particle size of the high-conductivity lithium iron phosphate material prepared in step S3 is 10 to 30 μm.

10. The method for preparing a high conductivity lithium iron phosphate material according to claim 4, characterized in that: In S1, the solid content of the mixed slurry is 30% to 50%.

Citation Information

Patent Citations

  • High-electric-conductivity lithium iron phosphate material and preparation method thereof

    CN109301195A

  • Composite conductive agent, preparation method thereof and application of composite conductive agent in positive electrode slurry

    CN109841834A

  • High-conductivity long-life lithium ion battery composite conductive paste and preparation method thereof

    CN117976905A

  • Preparation method of sulfur, nitrogen and boron co-doped lithium iron phosphate

    CN118894511A